Is stem design important in uncemented total hip replacement to decrease subsidence in obese patients? - Wyatt, Michael; Frampton, Chris; Hooper, Gary (Annals of Joint; Vol 2 (August 2017): Annals of Joint, 2017)
There has been a world-wide trend towards cementless total hip replacement (THR) over the last 20 years (1). One of the primary reasons for the introduction of the cementless stem was to improve the outcome in younger, more active patients, particularly males. The New Zealand Joint Registry (NZJR) has shown a revision rate of 0.89/100 component years (cy) for cementless THR’s in patients under 55 years compared to 1.73/100 cy for cemented THR and 0.90/100 cy compared to 0.98/100 cy for those between 55–65 years (P